Pseudogap in electron-doped cuprates: Strong correlation leading to band splitting - Masafumi Horio; Shiro Sakai; Hakuto Suzuki; Yosuke Nonaka; Makoto Hashimoto; Donghui Lu; Zhi-Xun Shen; Taro Ohgi; Takuya Konno; Tadashi Adachi; Yoji Koike; Masatoshi Imada; et al. (Proceedings of the National Academy of Sciences, 2025)
The pseudogap phenomena have been a long-standing mystery of the cuprate high-temperature superconductors. The pseudogap in the electron-doped cuprates has been attributed to band folding due to antiferromagnetic (AFM) long-range order or short-range correlation. We performed an angle-resolved photoemission spectroscopy study of the electron-doped cuprates Pr 1.3− x La 0.7 Ce x CuO 4 showing spin-glass, disordered AFM behaviors, and superconductivity at low temperatures and, by measurements with fine momentum cuts, found that the gap opens on the unfolded Fermi surface rather than the AFM Brillouin zone boundary. The gap did not show a node, following the full symmetry of the Brillouin zone, and its magnitude decreased from the zone-diagonal to ( π ,0) directions, opposite to the hole-doped case. These observations were reproduced by cluster dynamical-mean-field-theory calculation, which took into account electron correlation precisely within a (CuO 2 ) 4 cluster. The present experimental and theoretical results are consistent with the mechanism that electron or hole doping into a Mott insulator creates an in-gap band that is separated from the upper or lower Hubbard band by the pseudogap.